Effect of annealing on the viscoelastic behavior of poly(ether-ether-ketone). (3rd January 2019) - Jiang, Zhiyuan; Liu, Peng; Sue, Hung-Jue; Bremner, Tim
Abstract: Annealing is widely utilized in industry to manipulate the mechanical properties of semi-crystalline polymers. In this work, poly(ether-ether-ketone) (PEEK) was annealed at different temperatures above its glass transition temperature ( T g ) to investigate its influences on the viscoelastic behavior of PEEK. A set of master curves on long-term creep and stress relaxation behaviors of PEEK were obtained via time-temperature superposition and showed that a higher annealing temperature leads to more retardation. The underlying molecular mechanism is related to a higher activation energy of β-relaxation ( E β ) associated with the molecular motions below T g . A physics-based Ngai's Coupling model was chosen for the analysis, suggesting a higher degree of restriction on molecular mobility due to annealing, which is mainly attributed to the increases in the density of the amorphous phase and the crystallinity. Usefulness of the Ngai's Coupling model for the prediction of long-term viscoelastic behavior of semi-crystalline polymers is discussed. Graphical abstract: Highlights: Ngai's Coupling model fits the creep behavior of semicrystalline PEEK. E β responsible for molecular motions below T g is increased upon annealing. Annealing causes increase in ρ amorphous phase and χ c to restrict molecular mobility.